Computational Numerical Control (CNC) Machines: A Systematic Review From 2015 To 2022 (LACCEI, 2024)
The following systematic review tries to group together the most information about machines by computational numerical control (CNC) in order to find the benefits and limitations for the mechanical industry that will lead to optimize the approaches that have been addressed. The method that was carried out in the present work was the methodology based on the PRISMA strategy finding a total of 33 articles, which was divided into 5 approaches that are the following: production, manufacturing systematization, design and maintenance. The results show the impact of CNC machines on both benefits and limitations, in addition to the distribution of found items by years, countries and continental level.